Priapismus as Leukostasis Manifestation in Chronic Myeloid Leukemia - Wulyo Rajabto; Jane A.C. Djianzonie; Livy B Pratisthita; Hamzah Shatri (Acta Medica Indonesiana)
Chronic Myeloid Leukemia (CML) is a myeloproliferative disease characterized by the presence of Philadelphia chromosome or BCR-ABL oncogene fusion. Patients with CML commonly present in the chronic phase with chief complaint of abdominal pain or early satiety. Priapism as the first manifestation of CML is a rare phenomenon. Priapism as a consequence of leukostasis is a urological emergency that requires immediate intracavernosus therapy followed by systemic therapy. We report a 44-year-old male patient presenting with priapism as the first manifestation of CML.